Dietary Diversity in Nepal 2013-16. - Shively, Gerald.; Evans, Alecia.; Ghosh, Shibani.; Shrestha, Robin.; Webb, Patrick. (Tufts University. Tisch Library., 2019)
This presentation was from 6th Annual scientific Symposium in Nepal.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy